Surveillance of Antimicrobial Susceptibility Pattern of Chronic Suppurative Otitis Media in Tertiary Care Hospital of Southern Rajasthan - Lathi, Om Prakash; Sharma, Anshu; Maheshwari, Monika (Indian journal of otolaryngology, and head, and neck surgery, 2023)
The main aim of this work is to identify aerobic bacteriology and antibiotic sensitivity pattern of chronic suppurative otitis media in tertiary care hospital of southern Rajasthan. Two hundred and fifty clinically diagnosed cases of chronic suppurative otitis media of all age groups and both the sexes with the ear discharged of more than 6 weeks duration formed the subject of the study group. The specific identification of bacterial pathogens is done based on microscopic morphology, staining characteristics, cultural and biochemical properties using standard laboratory procedures. Antimicrobial susceptibility of the bacterial isolates to the commonly used antibiotics according to CLSI guideline is done by Kirby–Bauer disc diffusion method. Out of 250 cases, 226 (90.4%) were found to be smear positive and culture positive, 17 (6.8%) were found smear positive and culture negative, 7 (2.8%) were smear negative and culture negative. Pseudomonas spp was found the most common organism isolated was. Out of 244 isolates, 174 (71.3%) were found to be sensitive to Amikacin. In our study, Pseudomonas spp. 98% isolates were found to be most sensitive to Meropenem and 84.2% isolates were found to be most resistance to Ceftazidime. This study is useful to prevents the administration of unwanted antibiotics and in development of empirical policy. This may be helpful to medical practitioner for the prescribing antibiotics in the treatment of CSOM.